Kepemilikan Saham Suami dan Istri dalam Satu Perseroan Terbatas - Wishnu Kurniawan; Yeni Tan (Fakultas Hukum, Universitas Internasional Batam, 2016)
The purpose of this study is to investigate and analyze the validity on the ownership of Limited Liability Company by a husband and wife with joint property in Indonesia entailing towards the legislation on Limited Liability and legal consequences of shareholding of a limited liability company owned by a husband and wife with joint property in Indonesia. The research method used in this study is a normative legal research using library materials. The data used in this research is secondary data with primary legal materials, secondary and tertiary. The data retrieval technique used is the study of literature documents and interviews. The author used the method of data analysis by implementing qualitative approach. The results of this study showed that the shares within a limited liability company cannot be owned by a husband and wife without a prenuptial agreement on separating the marriage wealth fully. The reason being is because the establishment of the limited liability company supposed to be under the agreement. A limited liability company whose shareholders are a married husband and wife without a prenuptial agreement on separating the marriage wealth entirely, has indirectly violated the provisions of Law Number 40 Year 2007 on Limited Liability Company. In the case of loss, the shareholders shall be responsible towards the situation up to their personal wealth.